Chromatin landscape dynamics during reprogramming towards human naïve and primed pluripotency reveals the divergent function of PRDM1 isoforms - Jianfeng Zhou; Mingyue Guo; Guang Yang; Xinyu Cui; Jindian Hu; Tan Lin; Hong Wang; Shaorong Gao; Cizhong Jiang; Liping Wang; Yixuan Wang (Cell Death Discovery)
Abstract Induced pluripotent stem cells (iPSCs) technology holds great potential in both scientific research and clinical applications. It enables the generation of naïve and primed iPSCs from various cell types through different strategies. Despite extensive characterizations of transcriptional and epigenetic factors, the intricacies of chromatin landscape dynamics during naïve and primed reprogramming, particularly in humans, remain poorly understood. In this study, we employed ATAC-seq and RNA-seq analyses to delineate and compare the chromatin landscape of naïve and primed pluripotency through the human secondary reprogramming system. Our investigations revealed several key transcriptional and epigenetic factors pivotal for reprogramming-associated chromatin remodeling. Notably, we found two isoforms of PRDM1, PRDM1α, and PRDM1β, bind to distinct genomic loci and play different roles in the naïve reprogramming process. We proposed an auto-regulatory model explaining the distinct functions of PRDM1α and PRDM1β. Overall, our findings highlight the complexity and diversity of transcription factors in shaping chromatin landscape dynamics and directing the fates of pluripotent cells.